No involuntary treatment of mental illness in Australian and New Zealand prisons. Issue 1 (2nd January 2021) - Carroll, Andrew; Ellis, Andrew; Aboud, Andrew; Scott, Russ; Pillai, Krishna
ABSTRACT: Reflecting worldwide trends, as the prison population in Australia and New Zealand has risen over the past decade, the number of inpatient beds available for the involuntary treatment of mentally ill prisoners transferred from correctional custody has not increased commensurately. In this context, there have been calls to allow involuntary treatment of serious mental illness in prisons. This narrative review considers the extent of unmet psychiatric need within prisons in Australia and New Zealand and considers whether there is any evidence base for involuntary treatment of serious mental illness in prisons. The review concludes that the involuntary treatment of serious mental illness in custodial settings is likely to compromise clinical care, carries a significant risk of serious harms, encourages inappropriate management of prisoners and breaches human rights conventions. The authors found no evidence of improved clinical outcomes or any other benefits directly or indirectly linked to involuntary treatment of serious mental illness in correctional settings. Finally, the review describes the Prison Mental Health Service in the Australian jurisdiction of Queensland and suggests that this represents a 'best practice' model for the management of mentally ill prisoners.